Disinfection action of some essential oils on stainless steel - Vidács Anita (Review of faculty of engineering : analecta technica Szegedinensia, 2014)
Bacteria can attach to different surfaces and form biofilm. Biofilms can cause a big problem in food industry by contamination of food items and reduction of the effectiveness of machines. In the biofilm bacteria are less exposed to the different disinfectants, than the free living cells. Essential oils (EO) with known antimicrobial effect can also inhibit biofilm formation. In our experiments minimal inhibitory concentrations (MIC) and minimal bactericide concentrations (MBC) of the investigated EOs: cinnamon, juniper and lemon were determined by macro-dilution method on Pseudomonas putida and E.coli. Cinnamon showed the best antibacterial effect with MBC values of 2mg/ml forE. coli and 4mg/ml forP.putida. Thebactericidaleffect of EOsdependedontheactingtime. We established 80 minutes forP. putida and 120 (cinnamon EO) and 240 (juniper EO) min forE. coli. The disinfection potential of the EOs were studied on P. putida and E. coli 1 and 7 days old biofilms formed on industrial stainless steel surfaces. Each of the EO was effective. The number of P. putida cells was reduced up to 99% and we had similar result by 1 day old E. coli biofilm. The cell number of 7 days old E. coli biofilm was reduced by 62.5% with cinnamon EO and juniper EO reduced it by 87%.